Tingkat Pencemaran Udara dari Limbah Feses Kerbau Ditinjau dari Persepsi Masyarakat yang Bermukim di Sekitar Pasar Hewan Bolu, Kabupaten Toraja Utara - Sitti Nurani Sirajuddin (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the level of air pollution from fecal waste in terms of the perception of the people who live around the Bolu animal market, North Toraja Regency. This research was conducted from June 2022 to August 2022. The type of research used was descriptive research. . The number of samples used in this study were 22 respondents using purposive sampling method or chosen intentionally. Data collection methods used are observation and interviews. Analysis of the data used is descriptive analysis. The results showed that the level of air pollution from buffalo feces was disturbed according to the people who live around the Bolu Animal market, North Toraja Regency.